Asperolide A prevents bone metastatic breast cancer via the PI3K/AKT/mTOR/c‐Fos/NFATc1 signaling pathway - Wenli Jiang; Youlutuziayi Rixiati; Hao Huang; YiJun Shi; Caiguo Huang; Binghua Jiao (Cancer Medicine, 2020)
Abstract Background Breast cancer is the leading cause of death among women with malignant tumors worldwide. Bone metastasis is the main factor affecting the prognosis of breast cancer. Therefore, both antitumor and anti‐breast‐cancer‐induced osteolysis agents are urgently needed. Methods We examined the effect of Asperolide A (AA), a marine‐derived agent, on osteolysis and RANKL‐induced phosphoinositide 3‐kinase (PI3K)/AKT/mTOR/c‐FOS/nuclear factor‐activated T cell 1 (NFATc1) pathway activation, F‐actin ring formation, and reactive oxygen species (ROS) generation in vitro. We evaluated AA effect on breast cancer MDA‐MB‐231 and MDA‐MB‐436 cells in vitro through CCK8 assay, wound healing assay, transwell assay, Annexin V‐FITC/PI staining for cell apoptosis, and cell cycle assay. Furthermore, we assessed the effect of AA in vivo using a breast cancer‐induced bone osteolysis nude mouse model, followed by micro‐computed tomography, tartrate‐resistant acid phosphatase staining, and hematoxylin and eosin staining. Results Asperolide A inhibited osteoclast formation and differentiation, bone resorption, F‐actin belt formation, ROS activity, and osteoclast‐specific gene and protein expressions and prevented PI3K/AKT/mTOR/c‐FOS/NFATc1 signaling activation in a dose‐dependent manner in vitro. AA also inhibited breast cancer growth and breast cancer‐induced bone osteolysis by reducing osteoclast formation and function and inactivated PI3K/AKT/mTOR signaling in vivo. Conclusions Our study demonstrated that AA suppressed bone metastatic breast cancer. These findings indicate AA as a potential, novel curative drug candidate for patients with bone metastatic breast cancer.